(untitled) (ADVANCES IN MECHANICAL ENGINEERING AND TRANSPORT, 2019)
Continuous expansion of model ranges by leading automobile firms, creation of new types of cars demand establishment of qualification signs for the purpose of their division into classes. The absence of a single unified classification of road cars creates difficulties in the preparation of normative documents, writing scientific papers, reference and educational literature. This work is devoted to the development of the classification system of road cars and the creation of the corresponding software for the identification of modern brands of car models. Based on the segments formed in the work, the classification features of passenger cars were established. In addition to numerical parameters and designations, designations and class names were also proposed. The results of the work can be used for visualization, intelligent recognition; organization and regulation of road traffic, as well as provide an opportunity to facilitate the identification of vehicles on the roads of the European Union. The proposed classification system can be the basis for the creation of an appropriate standard with the participation of the international organization for standardization ISO. The results of the research can be effectively used during the design, construction of road transport infrastructure, production and sale of vehicles. They can become a regulatory framework for the implementation of financial transactions related to the operation of cars, namely: payments for parking, determining the cost of washing services, registration of tax payments, etc. Keywords: Classification of cars - Overall dimensions - Car base - Body type.